2014
DOI: 10.1186/s12866-014-0280-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the genetic regulation of the ECF sigma factor σS in Staphylococcus aureus

Abstract: BackgroundWe previously identified an ECF sigma factor, σS, that is important in the stress and virulence response of Staphylococcus aureus. Transcriptional profiling of sigS revealed that it is differentially expressed in many laboratory and clinical isolates, suggesting the existence of regulatory networks that modulates its expression.ResultsTo identify regulators of sigS, we performed a pull down assay using S. aureus lysates and the sigS promoter. Through this we identified CymR as a negative effector of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…4 B ). Previous studies have shown that CymR represses sigS expression and therefore may lead to its decreased activity ( 42 ). We confirmed this relationship as the SigS i-modulon activity was anticorrelated with the CymR i-modulon activity (Pearson R = −0.68, P = 8.23e-10) ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 B ). Previous studies have shown that CymR represses sigS expression and therefore may lead to its decreased activity ( 42 ). We confirmed this relationship as the SigS i-modulon activity was anticorrelated with the CymR i-modulon activity (Pearson R = −0.68, P = 8.23e-10) ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription in S. aureus depends on four sigma (σ) factors: σ A , the primary σ factor responsible for the transcription of most genes, σ B , involved in the general stress response, σ H , implicated in the competence state but cryptic in NCTC8325 (Morikawa et al, 2012 ), and σ S , the extracytoplasmic function sigma factor (Burda et al, 2014 ).…”
Section: Results and Hypothesismentioning
confidence: 99%
“…As with the SigB i-modulon, expression of the sigS gene correlated to activity of the ICA-derived SigS i-modulon (Pearson R = 0.77, p-value = 4.26e-22) ( Figure 4a ). Previous studies have shown that CymR represses sigS expression and therefore may lead to its decreased activity 41 . We confirmed this relationship as the SigS i-modulon activity was anti-correlated with the CymR i-modulon activity (Pearson R = -0.68, p-value = 8.23e-10) ( Figure S4c ).…”
Section: Gems Compute a Flux-balanced State That Reflect Regulatory Amentioning
confidence: 99%